DEVELOPMENT OF SCHOOLCHILDREN’S COMPETENCE TESTING TOOLS - Yefremova, N.F. (Pedagogy of Higher and Secondary Education, 2004)
The author defines the notion of competence and analyses ways of developing student’s competence. The advantages of test teaching technologies are examined.